Genital ulcers in Kenya. Clinical and laboratory study. Issue 6 (December 1981) - Nsanze, H; Fast, M V; D'Costa, L J; Tukei, P; Curran, J; Ronald, A
Abstract : Of 97 patients with genital ulcers attending a special treatment clinic in Nairobi, Kenya, 60 harboured Haemophilus ducreyi, four herpes simplex virus, and five Neisseria gonorrhoeae. Eleven patients had serological evidence of syphilis; of these one case was confirmed by darkfield microscopy. In the remaining cases no aetiological agent was identified. An enriched chocolate agar with vancomycin and serum was a useful medium for primary isolation of H ducreyi. Tetracycline was generally ineffective in the treatment of ulcers, but sulfadimidine was successful in almost 80% of cases.